2001
DOI: 10.1086/323424
|View full text |Cite
|
Sign up to set email alerts
|

Yield of Large‐Volume Blood Cultures in Patients with Early Lyme Disease

Abstract: To improve yield, 6 3-mL plasma cultures (18 mL total) were established for adult patients with early Lyme disease associated with erythema migrans. Borrelia burgdorferi was recovered from the blood of 22 (44.0%) of 50 evaluable patients. The recovery rate per plasma culture and the frequency of positive results for plasma cultures for individual patients were consistent with a level of spirochetemia of approximately 0.1 cultivable cell/mL of whole blood. Our findings suggest that, if further improvements in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
81
0
2

Year Published

2005
2005
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(89 citation statements)
references
References 10 publications
2
81
0
2
Order By: Relevance
“…Similar results were obtained with clinical and laboratory criteria, and the 64% frequency of disseminated disease is consistent with previous reports (36). However, since spirochetal dissemination may occur in the absence of symptoms and since dissemination is intermittent (36), it is likely that some patients who were clas- sified as not having evidence of disseminated disease did in fact have spirochetal dissemination. As previously noted (27,37), we found that some B. burgdorferi strains were more often associated with clinical or laboratory evidence of dissemination than others.…”
Section: Discussionsupporting
confidence: 91%
“…Similar results were obtained with clinical and laboratory criteria, and the 64% frequency of disseminated disease is consistent with previous reports (36). However, since spirochetal dissemination may occur in the absence of symptoms and since dissemination is intermittent (36), it is likely that some patients who were clas- sified as not having evidence of disseminated disease did in fact have spirochetal dissemination. As previously noted (27,37), we found that some B. burgdorferi strains were more often associated with clinical or laboratory evidence of dissemination than others.…”
Section: Discussionsupporting
confidence: 91%
“…Laboratory verification of Lyme borreliosis (LB) relies mainly on serology, because culture of the causative agent from clinical samples or PCR-based methods seem to be too insensitive and therefore unfeasible in clinical practice Sigal, 1998;Wormser et al, 1998). For serologic confirmation of Borrelia burgdorferi infection, a two-step approach with ELISA as a screening test and Western blotting as a confirmatory test is recommended by the Centers for Disease Control (CDC) (Brown et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…However, when accepted signs and/or symptoms are unsatisfactory or inconclusive, laboratory testing may be needed for improving diagnostic certainty. Serologic testing is the mainstay for laboratory-based diagnosis, although modern technologies have provided other tools that variably contribute, including PCR and culture (5,9,10,15). The utility of specific laboratory diagnostics, culture in particular, has also been emphasized given the need for gold standards for evaluation of new diagnostic tests and for use in laboratory authentication of Lyme disease in investigations of new treatments and vaccines (10)(11)(12).…”
Section: Discussionmentioning
confidence: 99%
“…The utility of specific laboratory diagnostics, culture in particular, has also been emphasized given the need for gold standards for evaluation of new diagnostic tests and for use in laboratory authentication of Lyme disease in investigations of new treatments and vaccines (10)(11)(12). The utility of high-volume blood cultures for diagnosis of Lyme disease has been primarily advanced by a single investigational group (15). The studies reported here using similar methodologies strongly support this approach for in vitro recovery of B. burgdorferi as a definitive diagnostic method.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation